Social and Solidary Economy: Mith or Reality? - Martínez Valle, Luciano (2009)
This article examines the social and solidary economy with a view to clarifying misunderstandings and outlining some of its limitations.  The article begins by analysing the contradictions and difficulties included in the term “solidary economy” itself. Then it questions some of the elements presents in this theory: its utopianism, productive heterogeneity, the distinct perspectives from which it can be understood, and the ultimate economic objectives it seeks to attain, and  the  way  in  which  the  social  and  solidary  economy  relate  to  the  mercantile  and  public economies. The article will revisit some of the obstacles that have emerged out of the concrete case studies examine in the articles included in the previous dossier of Íconos (Nº 33).